2007
DOI: 10.1093/brain/awl324
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid dynamics between the intracranial and the subarachnoid space of the optic nerve. Is it always bidirectional?

Abstract: CSF is thought to flow continuously from the site of production in the ventricles into interconnected spaces; i.e. cisterns and subarachnoid spaces (SASs). Since the SAS of the optic nerve is defined by a cul-de-sac anatomy, it is not evident how local CSF might recycle from that region to the general SAS. The concept of free communication of CSF has recently been challenged by the description of a concentration gradient of beta-trace protein, a lipocalin-like prostaglandin d-synthase (L-PGDS), between the spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
182
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(195 citation statements)
references
References 52 publications
7
182
0
6
Order By: Relevance
“…Moreover, we have tested our measurements at the same position in all the patients, while the MRI study searched for the wider ONSD section area. Data from both retrospective and prospective studies suggest that peripherally measured ICP is diminished in NTG patients when compared to other neurologic patients [18,19]. While there is a possibility for the underlying neurological condition to have an impact on the ICP, one would expect ONSD to be decreased in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have tested our measurements at the same position in all the patients, while the MRI study searched for the wider ONSD section area. Data from both retrospective and prospective studies suggest that peripherally measured ICP is diminished in NTG patients when compared to other neurologic patients [18,19]. While there is a possibility for the underlying neurological condition to have an impact on the ICP, one would expect ONSD to be decreased in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…54 Authors performed MRI and CT-cisternography and compared albumin, IgG, x-trace protein, and brain-derived protein lipocalin-like prostaglandin D-synthase content. From differences in ratios of CSF proteins in optic nerve vs the lumbar region, and cisternography, they concluded that CSF flow compartmentalized in the optic nerve under these pathological conditions.…”
Section: Haemodilutionmentioning
confidence: 99%
“…Histological examination of the meninges of the human optic nerve showed the perioptic SAS most narrow in the intracanalicular region. 7 In view of the anatomical features and our observation of notable SAS dilation at the intraorbital region, a check valve phenomenon at the intracanalicular region may have caused local CSF entrapment. 8,9 Another possible explanation is impaired CSF absorption.…”
Section: Discussionmentioning
confidence: 84%
“…Owing to the cul-de-sac structure, CSF dynamics between the intracranial SAS and the SAS of the optic nerve remain to be determined in detail. 7,9 Killer and colleagues reported that lymphatics present in the optic dura oŠers an out‰ow pathway of CSF at the optic nerve sheath. 10 In our case, MR imaging demonstrated enhancing dura mater along with the optic nerve sheath.…”
Section: Discussionmentioning
confidence: 99%